Simulating the hydrologic response when streams are incorporated in valley-fill design. Issue 5 (2nd September 2016) - Hopkinson, L.C.; Sears, A.E.; Snyder, M.; O'Leary, E.; DePriest, N.; Quaranta, J.D.; Ziemkiewicz, P.F.
Abstract: The geomorphic landform design (GLD) approach has the potential to incorporate stream networks into valley-fill reclamation. This work modelled the potential hydrologic response of GLD by evaluating storm response as well as flooding of the receiving reach of one West Virginia valley fill in several construction phases (i.e. pre-mining, conventional design and GLD). The GLD during construction condition resulted in peak flowrates that were more than twice the undisturbed pre-mining condition, but peak flowrates reduce to pre-mining conditions over time. A GLD that included surface ponds was presented to offer on-site streamflow. A retrofit example was presented to improve bond failing sites.